2021 European Thyroid Association Guideline on Thyroid Disorders prior to and during Assisted Reproduction. Issue 6 (21st February 2021) - Poppe, Kris; Bisschop, Peter; Fugazzola, Laura; Minziori, Gesthimani; Unuane, David; Weghofer, Andrea
Abstract : Severe thyroid dysfunction may lead to menstrual disorders and subfertility. Fertility problems may persist even after restoring normal thyroid function, and then an assisted reproductive technology (ART) may be a solution. Prior to an ART treatment, ovarian stimulation is performed, leading to high oestradiol levels, which may lead to hypothyroidism in women with thyroid autoimmunity (TAI), necessitating levothyroxine (LT4) supplements before pregnancy. Moreover, women with the polycystic ovarian syndrome and idiopathic subfertility have a higher prevalence of TAI. Women with hypothyroidism treated with LT4 prior to ART should have a serum TSH level <2.5 mIU/L. Subfertile women with hyperthyroidism planning an ART procedure should be informed of the increased risk of maternal and foetal complications, and euthyroidism should be restored and maintained for several months prior to an ART treatment. Fertilisation rates and embryo quality may be impaired in women with TSH >4.0 mIU/L and improved with LT4 therapy. In meta-analyses that mainly included women with TSH levels >4.0 mIU/L, LT4 treatment increased live birth rates, but that was not the case in 2 recent interventional studies in euthyroid women with TAI. The importance of the increased use of intracytoplasmic sperm injection as a type of ART on pregnancy outcomes in women with TAI deserves more investigation. For all of the above reasons, women of subfertile couples should be screened routinely for the presence of thyroid disorders.